Do nursing staff encourage functional activity among nursing home residents? A cross-sectional study of nursing staff perceived behaviors and associated factors. Issue 1 (December 2017) - Kuk, Nienke; den Ouden, Mirre; Zijlstra, G.; Hamers, Jan; Kempen, Gertrudis; Bours, Gerrie
Abstract Background Nursing home residents are mainly inactive. Nursing staff can encourage residents to perform functional activities during daily care activities. This study examines 1) the extent to which nursing staff perceive that they encourage functional activity in nursing home residents and 2) the associations between these nursing behaviors and professional characteristics, contextual factors, and information-seeking behaviors. Methods In this cross-sectional study, 368 registered nurses and certified nurse assistants, working in somatic and psychogeriatric wards of forty-one nursing homes throughout the Netherlands participated. Self-reported data were collected with a questionnaire, comprising the MAINtAIN-behaviors, which assesses the extent to which nursing staff encourage functional activities, including different activities of daily living (ADL), household activities, and miscellaneous encouraging activities (e.g., discouraging informal caregivers from taking over activities residents can do themselves). Additional data collected included professional characteristics (e.g., age), contextual factors (e.g., ward type), and information-seeking behaviors (e.g., reading professional journals). Descriptive statistics were used to determine the extent to which functional activities were encouraged. Hierarchical linear regression analyses were performed to determine the associations between the encouragement of functional activities and other factors. Results Nursing staff perceived that household activities (mean 4.1 (scale range 1–9), SD 1.9) were less often encouraged than ADL (mean 6.9, SD 1.2) or miscellaneous activities (mean 6.7, SD 1.5). The percentage of nursing staff stating that different household activities, ADL, or miscellaneous activities were almost always encouraged ranged from 11 to 45%, 41 to 86%, and 50 to 83% per activity, respectively. The extent to which these activities were encouraged differed for some of the professional characteristics, contextual factors, or information-seeking behaviors, but no consistent pattern in associations emerged. Conclusions According to nursing staff, household activities are not as often encouraged as ADL or miscellaneous activities. Professional characteristics, contextual factors, and information-seeking behaviors are not consistently associated with the encouragement of functional activity. Nursing staff should also focus on improving the encouragement of household activities. Future research could examine the role of other factors in encouraging functional activity, such as experienced barriers, and assess to what extent the perception of nursing staff corresponds with their actual behavior.